Changing Prescribing Patterns Through Early Identification of High Risk Patients - Amato, Ashley (My University, 2018)
The prescription drug use/abuse epidemic is increasing within the United States, and has affected 12.5 million Americans and the U.S. economy with an estimated $50 billion/year in lost wages, productivity, and criminal expenses. Opiate addiction related deaths have increased drastically in the past five years. Opiates have become the most prescribed medication to treat chronic pain. Opiate addiction is correlated with poor coping mechanisms and providers are struggling with having enough knowledge to treat chronic pain appropriately and be alert for aberrant behaviors and high risk patients. Practices for writing opiate prescriptions include the practitioner’s clinical judgment and site pain management protocols; consisting of a urine drug screen and the prescription monitoring program. For 90 days prior to implementation, a retrospective chart review was completed on all chronic pain patients, ages 18-64. Medications prescribed and follow ups scheduled were examined. Prior to implementation, an educational in-service was given to the providers to educate them on the use of the Screener and Opioid Assessment for Patients with Pain (SOAPP) tool and prescribing guidelines. Over 90 days, the SOAPP tool was administered to all patients meeting eligibility criteria and medication prescribed and follow up scheduled were reviewed. Feedback was assessed by the use of a PDSA tool. Pre and post data collected were uploaded and a comparative analysis conducted. Pre-intervention mean SOAPP score was 9.78 and the mean standard deviation was 3.14. There was a distinct change in prescriptions written and follow up scheduled.
Keywords: opioid addiction prevention, patient screening tools